2014
DOI: 10.3126/jfstn.v8i0.11752
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Cultural Conditions for the Production of Pectinase from Selected Fungal Strain

Abstract: Pectinase are the group of enzymes that catalyze the degradation of pectin substances through de-polymerisation and de-esterification. This study is concerned on the isolation, screening and selection of suitable strain of pectinolytic organism and optimization of cultural conditions for the biosynthesis of pectinase. From the soil samples collected from Lalitpur, Kathmandu, Gulmi, Manang and Dang, 18 fungal colonies were isolated on the basis of halozone formation on Potato dextrose agar and identified. Enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…A low fermentation time of 2 and 3 days was observed for the production of the invertases from the Saccharomyces cerevisiae [42] and L-asparaginase by Trichoderma viride Pers: SF Grey [57], respectively. The higher incubation time of 7 days was also noted for the production of pectinases by Aspergillus niger [20], cellulases by Penicillium sp.…”
Section: Time Course Study For the Industrial Enzymes Production By Microorganismsmentioning
confidence: 69%
See 3 more Smart Citations
“…A low fermentation time of 2 and 3 days was observed for the production of the invertases from the Saccharomyces cerevisiae [42] and L-asparaginase by Trichoderma viride Pers: SF Grey [57], respectively. The higher incubation time of 7 days was also noted for the production of pectinases by Aspergillus niger [20], cellulases by Penicillium sp.…”
Section: Time Course Study For the Industrial Enzymes Production By Microorganismsmentioning
confidence: 69%
“…The industrial enzyme-producing microorganisms are generally isolated from soil samples collected from various places [4][5][6][7][8][9][11][12][13][15][16][17]18,[20][21][22]24,26,27,[31][32][33][34][35]. They are also obtained from plant bark [25]), watery environment [36,37], skim milk [3]), marine sediment [38][39][40][41], municipal solid wastes [14] and from grapes [42] (Table 1).…”
Section: Isolation and Screening Of Industrial Enzyme-producing Microorganismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Palaniyappan et al (2009) found that the maximum pectinase activity of 5.17 and 5.84 U/ml with Aspergillus niger MTCC 281 using 1 % wheat flour and corn flour as substrates. Similarly, Rajiv Dhital et al (2013) reported that the maximum pectinase production was observed on the yeast glucose pectin media enriched with pectin at the concentration of 1.5 % which was 21 U/ml by soil fungal isolate (MG1).…”
Section: Resultsmentioning
confidence: 86%